Modeling of Compliance Processes with Specified Criteria in Complex Dynamic Systems - Ruben B. Aghajanyan (Изд-во НАН РА)
The urgency of research and modeling of complex systems lies in the fact that it is necessary to effectively manage such systems, to predict their development, to use corrective and preventive actions, to eliminate undesirable phenomena. It is necessary to ensure that the system parameters meet the specified requirements and criteria [1],[2] ,[3],[4] . The complexity of research and modeling of such systems is as follows: - Increase in the number of components and links in the system - Complication of internal random relationships - Existence of stochastic processes - Changes in the requirements for compliance of key indicators with specified criteria. The considered class of complex systems is encountered in practice in a number of industries in which strict requirements are imposed on the parameters of the system, to their estimates.
Keywords: Mathematics